2020
DOI: 10.7150/jca.35003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the benefits of celecoxib combined with anticancer therapy in advanced non-small cell lung cancer: A meta-analysis

Abstract: Background: Studies have reported that advanced NSCLC benefits from celecoxib combined with systematic treatment. However, the optimal combination with different treatments remains unclear. A meta-analysis was conducted to explore treatment combinations. Methods: We searched the relevant literature via PubMed, EMBASE, the Cochrane Library and PMC. The data for the overall response rate (ORR), overall survival (OS), progression-free survival (PFS), and adverse effects were obtained. Subgroup analysis was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In addition, the therapeutic effect of COX-2-inhibitors such as celecoxib has already been studied in other cancer types extensively [63]. However, COX-2 is not a routine target in modern oncology due to controversial results, e.g., for colorectal [64][65][66] and lung cancer [67,68]. For MPM on the contrary COX-2-inhibitors achieved promising results in vitro [35,57,69,70] and in vivo [36,71].…”
Section: Cox-2mentioning
confidence: 99%
“…In addition, the therapeutic effect of COX-2-inhibitors such as celecoxib has already been studied in other cancer types extensively [63]. However, COX-2 is not a routine target in modern oncology due to controversial results, e.g., for colorectal [64][65][66] and lung cancer [67,68]. For MPM on the contrary COX-2-inhibitors achieved promising results in vitro [35,57,69,70] and in vivo [36,71].…”
Section: Cox-2mentioning
confidence: 99%
“…Celecoxib is a selective inhibitor of COX-2. Clinical trials targeting patients with advanced NSCLC showed that celecoxib is effective in combination with immune checkpoint inhibitors and targeted therapies but also increases the risk of adverse effects such as hematological toxicity and cardiovascular complications [ 56 ]. Additional strategies to regulate COX-2-derived PGE 2 are essential to optimize and maximize the clinical benefits of non-targeted therapies such as NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhang et al showed that the crucial signaling altered in NSCLC was EGF receptor (EGFR). Also, they demonstrated that the use of CXB improves the overall response rate (ORR) ( 146 ). Therefore, more studies are required to describe the best therapeutic regimen according to the potential synergism between chemotherapeutic or immunotherapeutic strategies with CXB as an adjuvant.…”
Section: Discussionmentioning
confidence: 99%